(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
A case of 38-year-old woman who had a history of hypothyroidism and was receiving regular treatment reported feeling depressed and persistent sadness from three months. She was presented with associated symptoms of fatigue, lack of interest in everyday activities, insomnia, concentration problems, palpitations, and restlessness. Depression was confirmed by laboratory tests and clinical evaluation, and it later developed into generalized anxiety disorder (GAD). To find and treat possible causes of her anxiety symptoms, supportive care and management techniques were started. This case highlights the connection between hypothyroidism and mood disorders, showing how endocrine comorbidities can make people more vulnerable to anxiety and depression. Improving patient outcomes in these situations requires early detection and integrated management.